2006
DOI: 10.1227/01.neu.0000205287.06739.e1
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cell Opening and Prolapse of Struts of a Neuroform Stent in Curved Vasculature:Value of Angiographic Computed Tomography: Technical Case Report

Abstract: Increased opening of cells and prolapsing of struts of an open cell design stent can occur after placement in a curved vessel across an aneurysm orifice. Angiographic computed tomography is a new imaging tool that provides visualization of intracranial stents that is superior to digital subtraction angiogram or nonsubtracted images. It will enhance our understanding of stent behavior in clinical practice and improve the efficacy and safety of intracranial stent placement. Further in vitro and in vivo imaging s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 5 publications
0
55
0
Order By: Relevance
“…Most commonly, herniation is observed within the neck of an aneurysm. 16 On the other hand, closed-cell stents, such as the Enterprise vascular reconstruction device, may ovalize or kink (case 4) when implanted around tight bends. 13 CBCT allows the in vivo detection of this malapposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most commonly, herniation is observed within the neck of an aneurysm. 16 On the other hand, closed-cell stents, such as the Enterprise vascular reconstruction device, may ovalize or kink (case 4) when implanted around tight bends. 13 CBCT allows the in vivo detection of this malapposition.…”
Section: Discussionmentioning
confidence: 99%
“…Prior investigators have capitalized on this increase in spatial resolution to show that CBCT is capable of depicting neurovascular SESs with good detail in vitro and in vivo. 13,16,22,25,26 Other work has shown that CBCT has the contrast resolution required to provide simultaneous visualization of BES and a contrast-opacified host vessel, though at relatively lower detail. 23 The refined technique we present here demonstrates that contrast-enhanced CBCT can reliably provide detailed images of the newer generation of neurovascular stents, particularly lowvisibility SESs, in conjunction with their host arteries.…”
Section: Discussionmentioning
confidence: 99%
“…10 During the last 2 years, early case-based reports of the use of flat-panel detector angiographic equipment having the capability of volumetric soft-tissue imaging have described the capabilities of these systems to detect intracranial hemorrhages and to visualize endoluminal devices and their relationship to the arterial wall and lumen. [11][12][13] Although currently available C-arm CT lacks the temporal resolution to assess cerebral blood flow (CBF) or mean transit time, it does provide spatial resolution and contrast sensitivity that should be adequate to measure levels of blood in brain parenchyma (ie, CBV). [14][15][16] Our purpose was to test the hypothesis that in normal canines, CBV could be measured by using C-arm CT and that these measurements would correlate with those made by using PCT.…”
mentioning
confidence: 99%
“…Though introduced as a tool in dentistry, CBCT has found numerous applications in other medical fields, mainly interventional radiology as well. It is widely used to identify the correct location of artery for chemoembolization in hepatocellular carcinoma [3], prostate artery embolisation in benign prostate hypertrophy [4], during placement of intracranial and extracranial stents [5], abscess drainage, adrenal vein sampling for adenoma [6], identification of tissue infarcts in vascular anomalies and many other medical uses. The purpose of this article is to discuss and highlight the diagnostic applications of CBCT in various specialties of dentistry by means of a few cases which benefitted from its use.…”
Section: Introductionmentioning
confidence: 99%